A comparative study of anti-doping law on athletes in Malaysia and The United States / Fadzlin Syaqinna Mazlan...[et al.] - Mazlan, Fadzlin Syaqinna; Muhammad Muhiyuddin, Nurul Ashikin; Sharif, Nur Syafiqah; Zamani, Nursyafiqah (2013)
Doping is defined as the use of banned performance enhancing drugs, commonly happened in the area of sports. Most international sports organizations, especially the International Olympic Committee considered doping as an unethical practise. However, based on the arguments of the ethicists, this definition is a little bit different from the use of new materials that are included in the construction of suits and sporting equipment, although there is similarity in terms of the function which is to aid performance and give competitors the unfair advantage. The problem that we are facing now in Malaysia is that we do not have specific law to assist the area of anti-doping that concerns athletes, in a standardized manner. The athletes received lack of exposure from the authorities where some of them think that the substances that they bought online were legal. Furthermore, the revision of a specific law also cannot be traced either in the present or the law that is going to be enacted in future. A new law responsible to review, draft and make law should be established by our country for the process to be equitable, fair and efficient. Due to the above problem, this research is conducted to review the existing rules made by the World Anti-Doping Agencies. Then we will evaluate the adequacy of existing regulations in Malaysia regarding anti-doping. From the research that we had conducted we want to develop the possible future law of antidoping in Malaysia by comparing the anti-doping law in Malaysia and in TheUnited States.